Somatismen als Kodierungsmittel in Konfliktdialogen - Valenčič Arh, Urška; Pavić Pintarić, Anita (Slavia Centralis, 2020)
In the paper we focus on somatisms that contain body parts as phraseological components and appear in conflicting dialogues in children’s and youth literary works. We assume that somatisms occur in descriptions of non-verbal behavior and emotional states of individual figures. The material consists of children's and youth literary works in German, Slovenian and Croatian published in the last twenty years. Each language is represented by seven works.
Keywords: somatisms; conflict dialogues; children’s and youth literature; kinegrams; emotions